Analisis Dampak Pencemaran Air Sungai Kahung terhadap Ekonomi Masyarakat Desa Belangian - Muhamad Nor Hakim; Muhammad Anshar Nur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The research was conducted to find out: 1. What is the value of the economic loss of Belangian village community due to the water pollution of the Kahung River. 2. What are the Government's efforts to overcome the water pollution of the Kahung River. This method uses the method of replacement cost and cost of illness and interviews against the Government. The results showed that the loss of the village community Belangian due to loss of water services average of Rp. 1.154.400/KK/year, and the cost of medical average-average of Rp. 39.032.26/KK/year. Total loss of society due to the water pollution of the Kahung river Rata – Average of Rp. 1.193.432/KK/year. The Government's efforts have been monitoring river water, counseling to the community, socialization to miners, dissemination about sanitation.